2021
DOI: 10.3390/ijerph18042097
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Opioid Misuse and Opioid Use Disorder among Patients with Chronic Non-Cancer Pain and Prescribed Opioids in a Pain Centre in France

Abstract: (1) Background: Chronic non-cancer pain (CNCP) remains a public health challenge around the world. Opioids (PO) have been increasingly used in the treatment of CNCP in the last 20 years. This study aimed to assess the prevalence of opioid misuse and prescribed-opioid use disorder (p-OUD) among patients with CNCP in a pain centre in France, and to analyse risk factors for moderate or severe p-OUD. (2) Method: A cross-sectional study was conducted, including patients consulting for pain management in the pain ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…No study has specifically assessed the prevalence of POM with the POMI scale, making it difficult to compare our results with the literature. Nevertheless, two French studies assessing OUD with the DSM-5 (not validated in French) showed a prevalence from 43% to 52% (Eiden et al, 2019;Guillou-Landreat et al, 2021), 26.5% in a German study (Just et al, 2019) and 34.9% in an American study (Boscarino et al, 2011). The study of Guillou-Landreat et al (Guillou-Landreat et al, 2021) also assessed POM with the POMI scale but provide no information on the percentage of POM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…No study has specifically assessed the prevalence of POM with the POMI scale, making it difficult to compare our results with the literature. Nevertheless, two French studies assessing OUD with the DSM-5 (not validated in French) showed a prevalence from 43% to 52% (Eiden et al, 2019;Guillou-Landreat et al, 2021), 26.5% in a German study (Just et al, 2019) and 34.9% in an American study (Boscarino et al, 2011). The study of Guillou-Landreat et al (Guillou-Landreat et al, 2021) also assessed POM with the POMI scale but provide no information on the percentage of POM.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, two French studies assessing OUD with the DSM-5 (not validated in French) showed a prevalence from 43% to 52% (Eiden et al, 2019;Guillou-Landreat et al, 2021), 26.5% in a German study (Just et al, 2019) and 34.9% in an American study (Boscarino et al, 2011). The study of Guillou-Landreat et al (Guillou-Landreat et al, 2021) also assessed POM with the POMI scale but provide no information on the percentage of POM. The reasons for the variability of prevalence between studies may be the differences in population, the scale used and methodology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, it has been estimated that nearly one million people are using some form of opioid; in France prescription opioid use between 2004 and 2017 at least doubled. 8 In Italy, an almost four-fold increase in opioid prescriptions has been documented between 2007 and 2015, potentially correlated to the observed reduction in the prescription of NSAIDs. 5 The most impactful consequences of long-term opioid treatment are the development of tolerance, physical and mental addiction and the potential risk of incurring a substance use disorder (SUD).…”
Section: Epidemiology Of Chronic Painmentioning
confidence: 99%